2019
DOI: 10.1002/ana.25649
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of anosognosia in alzheimer's disease and its relationship to amyloid

Abstract: Objective: Unawareness, or anosognosia, of memory deficits is a challenging manifestation of Alzheimer's disease (AD) that adversely affects a patient's safety and decision-making. However, there is a lack of consensus regarding the presence, as well as the evolution, of altered awareness of memory function across the preclinical and prodromal stages of AD. Here, we aimed to characterize change in awareness of memory abilities and its relationship to beta-amyloid (Aβ) burden in a large cohort (N = 1,070) of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
90
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(114 citation statements)
references
References 48 publications
16
90
1
5
Order By: Relevance
“…Interestingly, this latter study suggested that these two conditions (hypernosognosia and low ACD) may occur in succession along the preclinical phase of AD. Consistently, a recent longitudinal study [13] found that (i) a subset of individuals with preclinical AD who progressed to MCI showed a 'hypernosognosia' up to 1.6 years before MCI diagnosis; (ii) the participants with MCI who progressed to dementia showed low ACD, eventually constituting a clear anosognosia 3.2 years before the diagnosis of Alzheimer's dementia.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Interestingly, this latter study suggested that these two conditions (hypernosognosia and low ACD) may occur in succession along the preclinical phase of AD. Consistently, a recent longitudinal study [13] found that (i) a subset of individuals with preclinical AD who progressed to MCI showed a 'hypernosognosia' up to 1.6 years before MCI diagnosis; (ii) the participants with MCI who progressed to dementia showed low ACD, eventually constituting a clear anosognosia 3.2 years before the diagnosis of Alzheimer's dementia.…”
Section: Introductionsupporting
confidence: 68%
“…10,11]; (b) as the discrepancy between the patient's rating and the objective cognitive performance [e.g. 12,13]; (c) a combination of both [14]. These studies lead to discordant results.…”
Section: Introductionmentioning
confidence: 99%
“…However, ACD is defined in relation to the reference sample. Moreover, using the participantinformant discrepancy, Hanseeuw et al [58] show that although the subject's complaint is initially higher than the informant's, the gap between the two narrows to a reversal of this ratio about 1.6 years before the MCI diagnosis. Thus, there would be a period in which, although ACD has begun to decline, the participant can still be defined as SCD.…”
Section: Discussionmentioning
confidence: 99%
“…However, ACD is defined in relation to the reference sample. Moreover, using the participant-informant discrepancy, Hanseeuw et al [59] show that although the subject's complaint is initially higher than the informant's, the gap between the two narrows to a reversal of this ratio about 1.6 years before the MCI diagnosis. Thus, there would be a period in which, although ACD has begun to decline, the participant can still be defined as SCD.…”
Section: Discussionmentioning
confidence: 99%